2018
DOI: 10.1017/s0007114518002489
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of non-homogenised and homogenised vegetables added to rice-based meals on postprandial glycaemic responses and in vitro carbohydrate digestion

Abstract: The addition of vegetable to carbohydrate-based meals was shown to contribute to glycaemic management. The aim of this study was to investigate the impact of homogenisation on vegetables added to rice meals in terms of acute glycaemic responses (GR). In a randomised crossover trial, sixteen healthy volunteers completed thirteen test sessions, which included two sessions for glucose control, two for rice and nine for different vegetable-rice mixed meals: cooked pak choi and cooked rice (CP+R); cooked cauliflowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Lettuce has a harder texture than watercress. Zhu et al in their study showed that the vegetable's texture itself may play an important role in glucose response [30]. Furthermore, plant bioactive compounds may inhibit the activities of both α-amylase and α-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lettuce has a harder texture than watercress. Zhu et al in their study showed that the vegetable's texture itself may play an important role in glucose response [30]. Furthermore, plant bioactive compounds may inhibit the activities of both α-amylase and α-glucosidase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that lactucaxanthin may possess some potential anti-diabetic properties, since it could reduce blood glucose level by reducing the activities of both α-amylase and αglucosidase in the intestine and pancreas of streptozotocin-induced diabetic rats [32]. It should be noted that in some previous studies, changes in glucose and insulin responses have also been monitored during the first hour of intervention (15, 30, and 45 min) [22,30]. Accordingly, this was a limitation in our study, in a way that the concentrations of plasma variables were not measured before the first hour.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, has shown that preparation and type cooking of the vegetables also has an impact on the postprandial GR. 24 It has been demonstrated that non-blended low-fat cooked vegetables were shown to reduce the postprandial GR more effectively compared to blended vegetables. 24 One of the explanations for this could be because vegetable, in its full form, promotes longer chewing and eating time, which previously has been associated with reduced postprandial GR.…”
Section: Resultsmentioning
confidence: 99%
“…24 It has been demonstrated that non-blended low-fat cooked vegetables were shown to reduce the postprandial GR more effectively compared to blended vegetables. 24 One of the explanations for this could be because vegetable, in its full form, promotes longer chewing and eating time, which previously has been associated with reduced postprandial GR. 24 Apart from that, the presence of polyphenol and dietary fibre in vegetable also plays an important role in affecting the glycemic control as well.…”
Section: Resultsmentioning
confidence: 99%
“…For cumin and tamarind, we used dietary doses, whereas for corn silk we used two separate doses—the “high dose” consisting of an amount commonly used in traditional Chinese medicine, and a lower (one-half of the high) dose to assess whether this lower, “dietary” dose would still be effective in improving glycemic parameters. Moreover, there is now considerable evidence that the food form plays an important role in determining glycemic and/or insulinemic responses [21,22,23]. We therefore investigated all the test ingredients in two separate forms: (i) extracts consumed as a drink (D) with plain rice or (ii) extracts added into rice (R) during cooking and consumed with plain water.…”
Section: Introductionmentioning
confidence: 99%